Circadian rhythms may not influence the outcomes of thrombolysis in patients with ischemic stroke: A study from China. (2nd November 2018) - Ding, Jiayue; Bai, Zhuoxuan; Zhou, Da; Li, Xiangyu; Rajah, Gary Benjamin; Ding, Yuchuan; Han, Jie; Ji, Xunming; Meng, Ran
ABSTRACT: Circadian rhythms can affect physical or mental activities as well as the time of stroke onset. The impact of circadian rhythms on acute ischemic stroke (AIS) patients treated by recombinant alteplase (rt-PA) is still incongruent. This study aims to consider whether the outcomes of thrombolysis differ depending on stroke onset time and rt-PA infusion time in patients with AIS. A total of 447 AIS patients, who underwent rt-PA intravenous infusion within 4.5 hours after stroke onset, were enrolled in this study consecutively from June 2010 through December 2016. All of the patients were grouped based on the stroke onset time and rt-PA infusion time into two exact 12-hour intervals as daytime (06:01–18:00) and nighttime (18:01–06:00) and further divided into four subgroups at 6-hour time intervals (00:01–06:00, 06:01–12:00, 12:01–18:00 and 18:01–24:00). Major neurological improvement at 1 hour, 24 hours and 7 days, 7-day mortality rate and 24-hour hemorrhage transformation was recorded. The results showed that a total of 295 patients (66.4%) appeared with AIS and 252 (56.4%) were treated during daytime. Higher NIHSS at admission was observed when stroke occurred in nighttime, especially during 00:01–06:00. Patients with stroke onset in nighttime especially during 18:01–24:00 had a significant shorter onset-door time and onset-needle time. No differences of the major neurological improvement at 1 hour, 24 hours and 7 days, 24-hour hemorrhagic transformation and 7-day fatality rate were found among either 12-hour time frames or 6-hour time frames according to the time of stroke onset or rt-PA infusion. In conclusion, there was no evidence to predict that circadian rhythms could influence the outcomes of AIS patients treated with rt-PA in China, although stroke onset during nighttime might aggravate neurological impairment before treatment. Further, multicenter and prospective clinical trials with larger number of subjects are still needed to draw more reliable conclusions.